Pengaruh kepemilikan manajerial dan leverage terhadap nilai perusahaan dengan kinerja keuangan sebagai variabel intervening - Indah Royani; Rita Indah Mustikowati; Supami Wahyu Setyowati (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2020)
The purpose of this study is to find out how the influence of managerial ownership and leverage on firm value with financial performance as an intervening variable. This research is a type of quantitative research. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2018 period. Samples were selected using purposive sampling. The results showed that managerial ownership had no effect on firm value. Leverage affects the value of the company. Managerial ownership does not affect financial performance. Financial performance affects the value of the company. Managerial ownership does not affect the value of the company through financial performance. And leverage has no effect on company value through financial performance.